Terminal Sliding-Mode Control of Virtual Humanoid Robot with Joint Restrictions Walking on stepping objects. Issue 4 (18th May 2020) - Sanchez-Magos, M.; Ballesteros, M.; Cruz-Ortiz, D.; Salgado, I.; Chairez, I.
Abstract: This manuscript deals with the problem of controlling a virtualized humanoid robot with 16 degrees of freedom (DOF). The aim of this study was to design an output feedback discontinuous controller which must resolve the sequence of articulation movements to walk over disjoint stepping objects placed in front of the humanoid robot. The suggested controller considers the state restrictions, via a nonstandard strong Lyapunov function, corresponding to the angular displacements and velocities at each articulation. This study implements an extended state terminal second order sliding mode controller with time dependent gains, to ensure the finite-time tracking trajectory of each articulation of the humanoid robot. The terminal sliding mode (TSM) is implemented in a virtual platform developed in a computer-aided design software. For comparison purposes, the controller was compared with a state feedback and a first order sliding mode algorithms.